Development of educational games based on local wisdom to improve critical thinking and communication skills - Heri Wicaksono; Rayendra Rayendra; Abna Hidayati; Ulfia Rahmi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to develop and evaluate a local wisdom-based educational game to support the improvement of critical thinking and communication skills of fifth-grade elementary school students. The research addressed the limited availability of interactive learning media that integrate local cultural values and support 21st-century skills, particularly in IPAS learning. The game was developed by incorporating Sarolangun local wisdom within a Game-Based Learning (GBL) framework using the ADDIE model. Validation was conducted by media, content, and language experts, while practicality testing involved teachers and students. The effectiveness of the game was examined through pre- and post-assessments of students’ critical thinking and communication skills using structured instruments. Data were analyzed using descriptive quantitative and qualitative methods. The results indicated that the game achieved high validity scores (content 4.38, media 4.64, language 4.69) and very practical criteria based on teacher and student responses. Post-assessment results showed an improvement in students’ critical thinking and communication skills compared to pre-assessment. These findings suggest that the developed game is valid, practical, and has potential to support skill development while introducing local cultural values in elementary education.